2001
DOI: 10.1177/0011128701047001001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Legal Liabilities in Law Enforcement: Police Chiefs' Views

Abstract: Texas mandates 40 hours of law enforcement management and leadership training biannually for police chiefs. To implement this requirement, from October 1997 to August 1999, the Law Enforcement Management Institute of Texas held 22 statewide training classes. During the training, we administered a survey on legal liabilities in law enforcement, in which 808 usable surveys were completed. Amassing the largest data set on legal liabilities in law enforcement, this article reports results from that survey and docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 14 publications
5
62
1
Order By: Relevance
“…(Barker, 1999, p. 129) Conversely, Novak et al (2003) reached the conclusion that officers do not change their behavior in the face of civil suits. This finding has ample support in the literature in this area, for while studies have found police officers are in fact greatly concerned about civil litigation, it does not necessarily cause them to change their behavior (Garrison, 1995;Hughes, 2001;Kappeler, 2001;Scogin & Brodsky, 1991;Stevens, 2000;Vaughn & Coomes, 1995;Vaughn, Cooper, & del Carmen, 2001). Despite this fact, civil litigation is still believed to be a causative factor in police officers who engage in depolicing.…”
mentioning
confidence: 87%
“…(Barker, 1999, p. 129) Conversely, Novak et al (2003) reached the conclusion that officers do not change their behavior in the face of civil suits. This finding has ample support in the literature in this area, for while studies have found police officers are in fact greatly concerned about civil litigation, it does not necessarily cause them to change their behavior (Garrison, 1995;Hughes, 2001;Kappeler, 2001;Scogin & Brodsky, 1991;Stevens, 2000;Vaughn & Coomes, 1995;Vaughn, Cooper, & del Carmen, 2001). Despite this fact, civil litigation is still believed to be a causative factor in police officers who engage in depolicing.…”
mentioning
confidence: 87%
“…Officers will likely want to know if the department 'has their back' in the event of a negligent investigation lawsuit. In addition, there is the possibility that Hill will cause an increased fear of litigation among police officers and administrators (see, e.g., Hall et al, 2003;Vaughn, Cooper, & Carmen, 2001). …”
Section: Implications For Law Enforcementmentioning
confidence: 99%
“…Absent rigorous, planful methodologies in place in the near term, it is unlikely that any definitive conclusions about Hill's impact will be evident in the future. Prior research illustrates very clearly the difficult nature of research on civil litigation against police (see Archbold & Maguire, 2002;Hughes, 2001;Vaughn, Cooper, & del Carmen, 2001;Worrall, 1998). Assuming that authoritative conclusions can be retroactively determined from archival records is likely to be a major mistake.…”
Section: Implications For Law Enforcementmentioning
confidence: 99%
“…Managers should be aware that specialized subordinates are less liable when sued in civil litigation (M.S. Vaughn, Cooper, & del Carmen, 2001). Training and specialization can reduce employees' misbehavior (Walker et al, 2000) on and off-duty (M.S.…”
Section: Division Of Labormentioning
confidence: 99%